До історії перших багатотомних видань творів Івана Франка - Голяк, Т. (Слово і Час, 2008)
У статті зосереджено увагу на питанні виникнення задуму першого кількатомника та історії його
укладання й видання. Порушується проблема композиційної будови томів малої прози та принципів
укладання матеріалу в багатотомних виданнях літературної спадщини І.Франка згідно з принципом
творчої волі автора. This article provides some explanatory notes on the conception of the first multivolumed edition of
I.Franko’s works as well as essential comments upon its editing und publishing.
The author of the article outlines the problem of composition of volumes containing Franko’s short stories
and also characterises the principles underlying a complex structure of the multivolumed editions of I.Franko’s
works based upon the principle of the writer’s will. В статье особое внимание уделяется вопросу
возникновения плана первого многотомника,
истории его формирования и издания.
Рассматривается проблема композиционной
организации томов малой прозы и принципов
расположения материала в многотомных изданиях
литературного богатства писателя согласно
принципу последней творческой воли.